Workplace violence in the healthcare setting and its psychological impact on healthcare workers - Reuben Praharsh Kumar; Wincy Verghese; Divya Hegde; Smitha Lamiya Rasquinha; Rahul M. Rao; Ajay Kumar (Industrial Psychiatry Journal)
Background: Workplace violence (WPV) among healthcare workers (HCWs) poses a significant burden globally. Various studies have estimated the prevalence and characteristics of WPV, but few have assessed the impact in terms of the mental health of HCWs in the aftermath. Aim: To study the prevalence of WPV and its psychological impact on HCWs. In addition, we aimed to suggest strategies that can be implemented to prevent the overpowering burden of WPV. Materials and Methods: We used a standardized questionnaire developed by the International Labor Office to assess WPV, General Health Questionnaire (GHQ-12) to assess psychological distress, and a self-reported sleep quality scoring. Results: The study included 268 participants among which 43.7% reported having experienced WPV in the last 12 months, with 42.5% reporting verbal violence and 3.4% reporting physical violence incidents. Working in emergency services showed a significant association with experiencing verbal violence. There is also an underreporting of incidents of WPV. Among the psychological parameters, distress is significantly higher for both verbal and physical violence, and participants who faced physical violence had significantly lower sleep quality. Prevention strategies including adequate patient counseling, better communication, improved security, and stricter laws can be implemented to reduce violence. Conclusion: WPV in healthcare is very common in India with not only high prevalence rates but also a significant psychological burden. There is a need to develop better laws and implement policies to ensure a safe and healthy workplace for HCWs.